Modulation of NMDA receptor activity by CR4056, an imidazoline-2 receptor ligand with analgesic properties - Puja, Giulia; Losi, Gabriele; Rovati, Lucio; Lanza, Marco; Caselli, Gianfranco; Bardoni, Rita (Frontiers in Pain Research, 2022)
CR4056 is an imidazoline-2 receptor ligand having potent analgesic activity and synergistic effect with opioids. Very recently it has been found that CR4056 can revert the cognitive impairment in animal models of Alzheimer’s disease (AD). Since several lines of evidence highlight the importance of NMDAR modulators in nociceptive signaling and in AD progression, we considered as important to investigate the effects of CR4056 on NMDAR activity. In primary culture of cortical neurons, application of NMDA and glycine elicit a current that is decreased in a dose-dependent fashion by CR4056 (IC50 5.3 + 0.1 μM). CR4056 antagonism is reversible, not competitive, nor voltage dependent and is not blocked by pertussis toxin. CR4056 interacts with the co-agonist glycine site in a competitive way, indeed high glycine concentrations diminish its effect. Fibroblasts expressing different recombinant NMDA receptor are differently modulated by CR4056: the potency and the efficacy of the compound are higher in NR1-NR2B than in NR1-NR2A containing receptors. In lamina II neurons of spinal cord slices, single stimulation of afferent fibers evokes an NMDA-mediated current that is inhibited by 10 M CR4056. Repetitive stimulation of the dorsal root at high frequency and high intensity produces a firing activity that is significatively depressed by CR4056. Taken together our results broad the understanding of the molecular mechanisms of CR4056 analgesic activity involving the modulation of NMDAR activity. We propose that the analgesic action of CR4056 and the neuroprotective effects in AD models may be mediated also by NMDAR inhibition.